THE EFFECT OF CAPITAL STRUCTURE ON THE VALUE OF A BUSINESS ENTITY WITH QUADRATIC MODEL TESTING IN PROPEERTY, REAL ESTATE AND BUILDING CONSTRUCTION SECTORS - I Putu Suryawan; Putu Anom Mahadwartha (Journal of Management and Business, 2015)
The purpose of this study was to find empirical evidence on the effect of capital structure on the value of a business entity in accordance with the static trade-off theory. This study used a sample of enterprises in the property, real estate and building construction sector that are listed in the Indonesian Stock Exchange during the period of 2009-2012. The selection of the sample in this study using a non-probability sampling technique with the type of purposive judgment sampling. The samples used in this study are 160 during the years of observation. The method of analysis in this study is using quadratic regression. The findings in this study indicate that capital structure significantly influence the value of a business entity in accordance with the static tradeoff theory.